Meta-analysis of contribution of genetic polymorphisms in drug-metabolizing enzymes or transporters to axitinib pharmacokinetics - Brennan, Meghan; Williams, J. Andrew; Chen, Ying; Tortorici, Michael; Pithavala, Yazdi; Liu, Yingxue Cathy (European journal of clinical pharmacology, 2012)
Purpose Axitinib, an orally administered inhibitor of vascular endothelial growth factor 1, 2 and 3, is primarily metabolized by cytochrome P450 (CYP) 3A4/5 but is also a substrate for CYP1A2, CYP2C19, UDP-glucuronosyltransferase (UGT)1A1 and the drug transporters P-glycoprotein (encoded by the ABCB1 gene) and OATP1B1 (encoded by SLC01B1 ). The potential contribution of polymorphisms in genes encoding these enzymes and transporters to axitinib pharmacokinetic variability was assessed. Methods A fixed effects meta-analysis was performed using data pooled from 11 healthy volunteer clinical pharmacology trials to investigate the potential association between axitinib exposure and major polymorphisms in these genes following a 5-mg dose of axitinib. Results Up to 15 variant alleles were evaluated and up to 315 healthy volunteers per polymorphism were assayed. None of the polymorphisms analysed was a statistically significant predictor of axitinib pharmacokinetic variability. Amongst genotypes and inferred phenotypes, CYP2C19 genotype and the ABCB1 ( G2677T/A ) polymorphism were the closest to statistical significance in influencing axitinib pharmacokinetic variability after multiple-testing adjustment. However, no enzyme or transporter genotype/inferred phenotype contributed >5% to the overall pharmacokinetic variability of axitinib. Conclusions No statistically significant associations between the specific polymorphisms analysed and axitinib plasma exposure were observed, suggesting that genotype- or inferred phenotype-based adjustment of axitinib dose in individual subjects is not warranted.